ANTIBACTERIAL EFFECTIVENESS TEST of MINT LEAF EXTRACT (Mentha piperita L.) IN INHIBITING Stretococcus Sanguinis GROWTH - Herryawan; Rahmadaniah Khaerunnisa; Fadhilah Nuraini Fajri (Fakultas Kedokteran Gigi Unjani, 2021)
Streptococcus sanguinis (s.sanguinis) is one of the normal flora in the oral cavity. These bacteria act as a pioneer in forming plaques that cause most dental and oral diseases. It takes an antibacterial agent to be able to inhibit the clips of the plaque. One of the herbal plants that have been known to have antibacterial power is the mint leaf (Mentha Piperita L.). The antibacterial potency of this plant comes from its chemical compound content, such as flavonoids, polyphenols, tannins, and menthols. This study aimed to determine the inhibitory of mint leaf extract on the growth of Sanguinis. An experimental laboratory carries out research. Tests were carried out using the diffusion method in four test groups, namely mint leaf extract with a concentration of 2.5%, 5%, 7.5%, and 10%, and one control group that uses DMSO. Each treatment group repeated five times on the Mueller-Hinton media (MHA) using disk paper and incubated for 24 hours. The inhibition zone can be seen in the transparent area formed around the disk paper and then measured using the Sorong term to find a large diameter. Statistical analysis was carried out using the Kruskal-Wallis test. The study results that the largest inhibitory zone diameter was obtained in a test group with a concentration of 10% (16.39 mm), while the lowest diameter in the control group (4.89 mm) 10% concentration was the highest among all test groups. The DMSO did not have an antibacterial effect. The higher the concentration of an antibacterial compound, it will also increase its effectiveness. DOI : 10.54052/jhds.v1n1.p49-59